Behavioral Drivers Influencing Women’s Decision to Use Self-Injectable Contraception Provided by Community Health Surveillance Assistants in Rural Malawi - Martha Kamanga; Dilys Walker; Address Malata; Mandaachepa Nyando; Jessie Salamba; Alaizi Nkhoma; Innocencia Mtalimanja; Tamanda Jumbe; Emas Potolani; Alfred Maluwa; Chifundo Zimba; Josophine Changole; et al. (Women's Health Reports)
Introduction: Self-injection (SI) for contraceptive use is recommended for its proven ability to empower women and overcome barriers to contraceptive access. The World Health Organization endorsed SI as a self-care approach in 2019. Despite the increase in Malawi’s modern contraceptive prevalence rate from 38.1% in 2012 to 48.9% in 2020, it remains below the government’s 60% target. Injectable contraceptives, including depot medroxyprogesterone acetate subcutaneous (DMPA-SC), introduced in 2018, are the most popular contraceptive method in Malawi, particularly among adolescents, representing 49.8% of the contraceptive method mix. However, utilization of SI remains limited, especially in rural areas where access challenges persist. This study explores the behavioral drivers influencing women’s decision to use self-injectable contraception provided by community health surveillance assistants (CHSA) in rural Malawi. Methods: Using the capability, opportunity, motivation—behavior model, the study analyzed drivers of DMPA-SC SI adoption among 60 women aged 15–45 years in two rural districts, Mulanje and Ntchisi. Data were collected through in-depth interviews on women’s experiences with contraceptives, including SI. Results: Women's capability was strengthened as CHSAs addressed initial hesitation through practical demonstrations. Opportunity improved through enhanced access, trust, and privacy. Motivation increased with counseling, reduced travel costs, and CHSAs’ support, encouraging women to adopt self-injection confidently and consistently. Discussion: Women’s decisions to adopt SI were shaped by capability, motivation, and opportunity, with CHSAs playing a pivotal role. Future family planning programs should prioritize CHSAs’ training and deployment to improve SI uptake, fostering autonomy and accessibility for rural women.